Problem based learning in engineering education: a viable alternative for shaping graduates for the 21st century? - Mohd. Yusof, Khairiyah; Abdul Aziz, Azila; Abd. Hamid, Mohd. Kamaruddin; Abu Hassan, Mohd. Ariffin; Hassim, Mimi Haryani; Syed Hassan, Syed Ahmad Helmi; NMA, Azila (2004)
Engineering educators are faced with demands from various sectors to produce graduates who can be effective in today’s borderless k-economy. To accommodate these demands and adapt to changes in the 21st century, Problem Based Learning (PBL) is proposed as an alternative to traditional lectures in moulding engineering graduates to acquire the desired attributes. Although PBL has received a lot of attention, particularly in medicine, its implementation in engineering is not as encouraging. Engineering educators are sceptical that PBL is practical and applicable for engineering classrooms, given the high student to lecturer ratio, and the large body of knowledge that must be covered. Most importantly, can PBL really enhance learning and help students acquire the necessary generic skills? To investigate if PBL is a viable option for engineering education, a qualitative evaluation of outcomes in several undergraduate engineering classes, conducted using the PBL concept, was performed. The result of the study indicated that PBL can be adapted for engineering classrooms and induced the desired outcomes on the students. This paper discusses PBL, its benefits and potential in engineering education. However there are challenges faced by engineering educators in making the quantum leap from lecture-based classes to PBL.